2021
DOI: 10.3171/2021.3.focus2173
|View full text |Cite
|
Sign up to set email alerts
|

Existing clinical evidence on the use of cellular bone matrix grafts in spinal fusion: updated systematic review of the literature

Abstract: OBJECTIVE Spinal fusion surgery is increasingly common; however, pseudarthrosis remains a common complication affecting as much as 15% of some patient populations. Currently, no clear consensus on the best bone graft materials to use exists. Recent advances have led to the development of cell-infused cellular bone matrices (CBMs), which contain living components such as mesenchymal stem cells (MSCs). Relatively few clinical outcome studies on the use of these grafts exist, although the number of such studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…A review of initial spinal fusion clinical studies concluded that VBM grafts were safe for use in bone grafting since there were no adverse events associated with their use [ 22 ]. More recently, two systematic reviews concluded that use of VBMs for spinal fusion led to high fusion and low complication rates [ 23 , 24 ]. Specifically, 12-month fusion rates reported from using various VBMs in those studies ranged from 88–100% in cervical and 91–99% in lumbar patients, while per-level fusion ranged from 87–93% in cervical and 68–99% in lumbar segments [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of initial spinal fusion clinical studies concluded that VBM grafts were safe for use in bone grafting since there were no adverse events associated with their use [ 22 ]. More recently, two systematic reviews concluded that use of VBMs for spinal fusion led to high fusion and low complication rates [ 23 , 24 ]. Specifically, 12-month fusion rates reported from using various VBMs in those studies ranged from 88–100% in cervical and 91–99% in lumbar patients, while per-level fusion ranged from 87–93% in cervical and 68–99% in lumbar segments [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, two systematic reviews concluded that use of VBMs for spinal fusion led to high fusion and low complication rates [ 23 , 24 ]. Specifically, 12-month fusion rates reported from using various VBMs in those studies ranged from 88–100% in cervical and 91–99% in lumbar patients, while per-level fusion ranged from 87–93% in cervical and 68–99% in lumbar segments [ 23 , 24 ]. These findings align well with the results outlined in our study at 12-month evaluation for per-patient (88.1% cervical and 97.6% lumbar) and per-level fusion (98.5% cervical, 100% lumbar), with clinically meaningful improvements in pain and disability scores.…”
Section: Discussionmentioning
confidence: 99%
“…Musante et al reported 90% fusion success rates in patients undergoing PLF, with no significant difference in fusion rates among patients with and without risk factors to fusion [ 34 ]. In addition, Vivigen CBA (Depuy-Synthes, Raynham, MA, USA) has demonstrated high spinal fusion rates in multiple studies [ 35 ]. Multilevel posterolateral fusion with ViviGen demonstrated a fusion rate of 98.7% (graded via radiographs only) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vivigen (DepuySynthes, Raynham MA), have shown spinal fusion rates at 90% 27) . In a study of multilevel fusion in a posterolateral construct with CBA, the fusion rate was reported as 98.7% 15) .…”
Section: Discussionmentioning
confidence: 99%